Analysis of the electromagnetic field of multilayered biological objects for their irradiation in a waveguide system - Popriadukhin, Vadym; Popova, Iryna; Kosulina, Natalia; Cherenkov, Aleksandr; Chorna, Mariya (Eastern-European Journal of Enterprise Technologies, 2017)
We report theoretical study on the distribution of electromagnetic field in biological objects. To perform the analysis, we selected multilayer bio-objects the size less than a wavelength of the irradiating field. In order to investigate diffraction of electromagnetic wave on the biological objects of a given type, we used integral Maxwell equations in combination with boundary conditions both at the border of the object's layers and at the border of a guiding electrodynamic structure. A theoretical research into creation of a waveguide system was conducted for the irradiation of biological objects with dimensions less than a wavelength of the irradiating field. The waveguide system employed two diffusers: a biological object and a metallic sphere. Location of the bio-object was permanent while the sphere could move along a section of the waveguide. The result of research is the obtained dependence of reflectance coefficient on the distance between diffusers. Reflectance coefficient was obtained for frequency 58.6 GHz, waveguide dimensions d=10.668 mm, h=4.318 mm, radius of the metallic sphere 4 mm, dielectric permittivity of biological objects from 2 to 14 units the size Calculations showed that by selecting the distance between a bio-object and a metallic sphere, it is possible to achieve that the bio-object is located in the antinode of the electromagnetic field